Design and Pharmaceutical Evaluation of a Nano-Enabled Crosslinked Multipolymeric Scaffold for Prolonged Intracranial Release of Zidovudine - Sheri-Lee Harilall; Yahya E Choonara; Girish Modi; Lomas K Tomar; Charu Tyagi; Pradeep Kumar; Lisa C du Toit; Sunny E Iyuke; Michael P Danckwerts; Viness Pillay (Frontiers Media S.A., 2013)
Purpose. Nanomedicine explores and allows for the development of drug delivery devices with superior drug uptake, controlled release and fewer drug side-effects. This study explored the use of nanosystems to formulate an implantable drug delivery device capable of sustained zidovudine release over a prolonged period. Methods. Pectin and alginate nanoparticles were prepared by applying a salting out and controlled gelification approach, respectively. The nanoparticles were characterized by attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and dynamic light scattering (DLS) and were further evaluated for zidovudine (AZT) entrapment efficiency. Multipolymeric scaffolds were prepared by crosslinking carboxymethyl cellulose, polyethylene oxide and epsilon caprolactone for entrapment of zidovudine-loaded alginate nanoparticles to impart enhanced controlled release of zidovudine over the time period. Swelling and textural analysis were conducted on the scaffolds. Prepared scaffolds were treated with hydrochloric acid (HCl) to reduce the swelling of matrix in the hydrated environment thereby further controlling the drug release. Drug release studies in phosphate buffered saline (pH 7.4, 37°C) were undertaken on both zidovudine-loaded nanoparticles and native scaffolds containing alginate nanoparticles. Results. A higher AZT entrapment efficiency was observed in alginate nanoparticles. Biphasic release was observed with both nanoparticle formulations, exhibiting an initial burst release of drug within hours of exposure to PBS, followed by a constant release rate of AZT over the remaining 30 days of nanoparticle analysis. Exposure of the scaffolds to HCl served to reduce the drug release rate from the entrapped alginate nanoparticles and extended the AZT release up to 30 days. Conclusions. The crosslinked multipolymeric scaffold loaded with alginate nanoparticles and treated with 1% HCl showed the potential for prolonged delivery of zidovudine over a period of 30 days and therefore may be a potential candidate for use as an implantable device in treating Aids Dementia Complex. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.